Composition of Rift-Related Igneous and Sedimentary Rocks of the Keweenawan Supergroup in the Poersch No. 1, OZ-1, Finn, and Friederich Wells, Northeastern Kansas - Cullers, Robert L.; Berendsen, Pieter (Current Research in Earth Sciences, 1993)
A series of wells have been drilled up to a depth of 3,444 m (113,000 ft) into the midcontinent rift system (MRS) in northeastern Kansas. The age of a gabbro sill in the upper portion of the Precambrian rocks was determined to be 1,097.5 ± 3 Ma, and the magnetic polarity of the gabbro correlated to the lower Keweenawan rocks in the northern MRS (Van Schmus et al., 1990). The rocks below 2,259 m (7,411 ft) in the deepest well [Poersch no. 1, total depth 3,435 m (11,270 ft)] consist mostly of arkoses with subordinate amounts of shale, siltstone, and basalt. The rocks above 2,265 m (7,431 ft) in the Poersch well consist of basalt with minor siltstone, arkose, gabbro, and felsite. A proposed high-angle reverse fault could have juxtaposed the upper igneous rocks over the lower sedimentary rocks to produce a reversed stratigraphy. This would make the development of the southern MRS similar to that of the northern MRS. Thus, in the initial extensional phase of the MRS, broad subsidence coincided with abundant volcanism and little sediment production. Grabens formed in the later stages of rift development and were filled with abundant sedimentary rocks along with lesser volcanic rocks. The chemical characteristics of the basalts in the southern MRS are similar to those in the north. The southern basalts are subalkalic to alkalic and follow tholeiitic trends; a number of them are high-alumina basalts. Although there is a lot of scatter, Al2O3, Ni, and Cr concentrations decrease and Fe2O3, TiO2, K2O, rare earth elements, Ba, Hf, and Sc concentrations increase with decreasing Mg number. These trends are consistent with plagioclase, olivine, pyroxene, or spinel fractionation from primary basalts. One basalt could represent a primary magma because it has a high Mg number (0.68), high Ni (638 mg/kg) and Cr (233 mg/kg) concentrations, low incompatible element concentrations (e.g., La = 4.2 mg/kg), and a slight positive Eu anomaly. This possible primary magma could have formed by partial melting (20-25%) of an undepleted spinel peridotite at 30-40 km depth. Most basalts have not been contaminated by crustal rocks or silicic magmas. The mineralogy, chemical composition, and U-Pb geochronology of detrital zircons of the arkoses, siltstones, and shales are consistent with their derivation from the surrounding granitoid highlands with little or no input from the basalts. Even siltstones and arkoses within the mostly basaltic sequences are derived mostly from the granitoids, although the siltstones may have some input from the basalts (e.g., higher Ni concentration than the sandstones).